Designing the Distributed Model Integration Framework – DMIF. (August 2017) - Belete, Getachew F.; Voinov, Alexey; Morales, Javier
Abstract: We describe and discuss the design and prototype of the Distributed Model Integration Framework (DMIF) that links models deployed on different hardware and software platforms. We used distributed computing and service-oriented development approaches to address the different aspects of interoperability. Reusable web service wrappers were developed for technical interoperability models created in NetLogo and GAMS modeling languages. We investigated automated semantic mapping of text-based input-output data and attribute names of components using word overlap semantic matching algorithms and using an openly available lexical database. We also incorporated automated unit conversion in semantic mediation by using openly available ontologies. DMIF helps to avoid significant amount of reinvention by framework developers, and opens up the modeling process for many stakeholders who are not prepared to deal with the technical difficulties associated with installing, configuring, and running various models. As a proof of concept, we implemented our design to integrate several climate-energy-economy models. Highlights: Distributed model integration framework is developed. Distributed Computing and Service oriented software development approaches are used to develop the integration framework. Semantic mediation using an openly available Lexical Database and Ontology is discussed. Prototype of runtime model integration technique is discussed.